2019
DOI: 10.1038/s41598-018-35907-1
|View full text |Cite
|
Sign up to set email alerts
|

Variations in hydrodynamic characteristics of netting panels with various twine materials, knot types, and weave patterns at small attack angles

Abstract: It is essential to conduct hydrodynamic experiments for fishing gear at small attack angles along the flow direction to better understand the hydrodynamic characteristics of netting and application of gear. The hydrodynamic characteristics of netting panels made of different materials at small attack angles were investigated by a self-designed setup; this is essential for the effective use of netting on different types of gears. As confirmed by experiments, the measured drag of designed frame without netting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 15 publications
1
2
1
Order By: Relevance
“…This ratio was 13.32% (±0.42%), 14.51% (±0.54%), 15.05% (±0.49%), 15.60% (±0.46%), 15.47% (±0.35%), and 15.82% (±0.40%) for the codend without cutting ratio and the codends with cutting ratios 6:1, 5:1, 4:1, 7:2, and 3:1, respectively. However, the results reported by Tang et al [25,26] on netting showed that the frame drag force accounted for a maximum of between 17% and 20% of the total (netting drag + rigid frame drag) using streamlined frames, close to those obtained in this experiment. Therefore, the application of a rigid frame reduced the impact of turbulent or vortex flow on the experimental hydrodynamic force and the geometrical shape of codends.…”
Section: Effect Of Rigid Frame Drag Force On Codendsupporting
confidence: 89%
See 1 more Smart Citation
“…This ratio was 13.32% (±0.42%), 14.51% (±0.54%), 15.05% (±0.49%), 15.60% (±0.46%), 15.47% (±0.35%), and 15.82% (±0.40%) for the codend without cutting ratio and the codends with cutting ratios 6:1, 5:1, 4:1, 7:2, and 3:1, respectively. However, the results reported by Tang et al [25,26] on netting showed that the frame drag force accounted for a maximum of between 17% and 20% of the total (netting drag + rigid frame drag) using streamlined frames, close to those obtained in this experiment. Therefore, the application of a rigid frame reduced the impact of turbulent or vortex flow on the experimental hydrodynamic force and the geometrical shape of codends.…”
Section: Effect Of Rigid Frame Drag Force On Codendsupporting
confidence: 89%
“…This trend was confirmed by the experiment carried out in this study, demonstrating that the drag coefficient for the empty codend increased as the Reynolds number decreased and attack angle and cutting ratio increased. However, the drag coefficients obtained in this study are different from those obtained in the netting by Tang et al [25,26,34] and Hosseini et al [35], whereas they are similar to those obtained on the optimized trawls studied by Balash [30] and Thierry et al [6]. The main reason for this difference is that the mesh of the codend is in a free state in this experiment, rather than the mesh being tightly bound to the frame.…”
Section: Effect Of Cutting Ratio On the Net Shape And Drag Force Of Empty Codendscontrasting
confidence: 58%
“…The model trawl codends were selected and designed in model scale based on modified Tauti's law, with particular attention to the Antarctic fisheries. This codend model was designed based on a 1:20 scale (λ = 10) in the length scale of the codend model, a 1:3.6 small-scale (λ' = 3.6) in mesh size and twine diameter, and a 1:10.54 time ratio (τ = 10.54) using Tauti's law [25][26][27]. The codend was designed by assembling four pieces of netting using a mesh size of 40 mm and a twine diameter of 1.11 mm using polyethylene (PE) twine materials with diamond-shaped meshes.…”
Section: Codend Designmentioning
confidence: 99%
“…Empirical values for normal drag coefficients are proposed by Tsukrov et al (2011) for various types of copper netting, and Cha et al (2013) compared the drag coefficients of copper alloy nets with knotless fabric nets. In addition, the drag coefficients of nylon nets (Zhou et al, 2015) and knotless polyethylene nets (Tang et al, 2017;Tang et al, 2019) under different attack angles were studied. It is concluded that the normal drag coefficient is determined by the synergistic control of Reynolds number (Re) and solidity ratio, and the solidity ratio has a dual influence on the drag coefficient of inclined netting panels.…”
Section: Introductionmentioning
confidence: 99%